Population genomics of adaptation in Pseudomonas syringae - Nowell, Reuben William (The University of Edinburgh, 2015)
Horizontal gene transfer (HGT) and gene loss are important processes in the evolution of prokaryotic lineages. HGT involves the movement of genetic material between distantly related species, and can facilitate adaptation when gained genes confer advantageous phenotypes to recipient lineages. However, high levels of gene gain and loss are predicted to obfuscate patterns of vertical descent and homogenise nucleotide diversity across ecological and phylogenetic boundaries. Thus, a holistic understanding of the role of genome fluctuation in the emergence and maintenance of genetically and ecologically cohesive bacterial groups remains to be fully elucidated. In this thesis, I use the plant-associated bacterium Pseudomonas syringae as a model system to investigate the impact of HGT and gene loss on evolutionary processes such as adaptation, diversification and speciation. The Gram-negative Gammaproteobacterium P. syringae is an opportunistic plant pathogen, and has been used for decades as a model system with which to study the interaction between plants and their microbial pathogens. Recently, the diversification of lineages within this species has involved a number of host jumps onto a range of woody host plant species, resulting in the emergence of diseases such as bacterial canker of kiwi and bleeding canker of the European horse chestnut. Using whole-genome sequence data and a range of comparative genomics and phylogenetics methods, I quantitatively reconstruct the history of gene gain and loss in P. syringae and show HGT to be the predominant evolutionary force in this species. Genomes of this species are under constant permutation, are subject to a highly diverse HGT genepool and show marked differences in patterns of codon usage between imported and core genes. I then generate additional genome data for 26 strains of P. syringae that are pathogenic on a range of different woody plants, and investigate the contribution from HGT to the adaptation of these strains into the woody niche. Using a method that accounts for the underlying phylogenetic relationships among P. syringae strains, I look for the correlated evolution between gained genes and the woody niche, and find that a substantial proportion of the genome is associated with this ecological niche. I then investigate the recent adapitation of P. syringae pv. aesculi onto the European horse chestnut, and show that a number of genomic events that include both homologous and non-homologous recombination are likely to have led to the evolution of this bacterium onto its host, where it has become the causal agent of the bleeding canker disease that is currently epidemic across much of northern and central Europe. Overall, this thesis is an investigation into how HGT contributes to niche adaptation in P. syringae, and aims to further our understanding of the mechanisms that underlie bacterial evolution.
Keywords: population genomics; phytoadaptation; Pseudomonas syringae; HGT